Investigations of the spatial and temporal variations of Sr and Nd isotopes in sediments from two Indian Rivers: Implications to source identification. (15th April 2017) - Pradhan, Sonali; Zhang, Jing; Baskaran, Mark; Shirodkar, Prabhaker Vasant; Wu, Ying; Pradhan, Umesh Kumar
Abstract: Radiogenic isotopes of Sr and Nd provide crucial information on chemical and physical erosion processes, therefore used as tracers for fingerprinting the sources of fluvial sediments. Moreover, elemental geochemistry, 87 Sr/ 86 Sr and 143 Nd/ 144 Nd signatures in silicate fractions of sediments primarily reflect intricate controls of characteristics and provenance of sediment. A suite of sediment samples collected from two rivers of India, Narmada (large) and Netravati (small) were analyzed for elemental concentrations, 87 Sr/ 86 Sr and 143 Nd/ 144 Nd in silicate as well as acid‐leachable fractions. 87 Sr/ 86 Sr in acid‐leachable sediment fractions from both the rivers (0.7094 ± 0.0002 for Narmada and 0.7158 ± 0.003 for Netravati) showed more radiogenic 87 Sr/ 86 Sr in Netravati compared to Narmada indicating influence of source rocks in their watersheds. Weak correlation of sedimentary 87 Sr/ 86 Sr and 143 Nd/ 144 Nd with Al and Chemical Index of Alteration (CIA) in silicate fraction indicates that isotopic compositions are primarily controlled by their sources and not by chemical weathering in both the rivers. Provenance of sediments in Narmada is dominated by their supply from Deccan deposits with secondary supply from mid‐late Proterozoic Vindhyan along with Mesoproterozoic to Mesoarchean T DM Nd ages. Sediments from Netravati reflected signatures of peninsular gneisses dominant with gneisses schists and granodiorite along with Paleoarchean T DM Nd ages. Based on variability of 87 Sr/ 86 Sr and 143 Nd/ 144 Nd, present study highlight that sediment supplies from tributaries to the mainstream in Narmada is inadequate as compared to that in Netravati. 87 Sr/ 86 Sr and 143 Nd/ 144 Nd signatures in Narmada and Netravati are comparable with Global Rivers. Key Points: Evaluation of isotopic data on sediments in watershed of different size having contrasting geology Sr and Nd isotopes in watershed that are controlled by the source rocks in the catchment Data set provide new insight to the spatiotemporal variations on the modern river sediments